2016
DOI: 10.1002/jhbp.370
|View full text |Cite
|
Sign up to set email alerts
|

Minimal vascular flows cause strong heat sink effects in hepatic radiofrequency ablation ex vivo

Abstract: Minimal vascular flows of ≥1 ml/min cause a significant heat sink effect in hepatic RFA ex vivo. A lower limit for volumetric flow rate was not found. The maximum of the heat sink effect was reached at a flow rate of 10 ml/min and remained stable for flow rates up to 1,500 ml/min. Hepatic inflow occlusion should be considered in RFA close to hepatic vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
1
32
1
Order By: Relevance
“…Of note, RFA still exhibits some limitations in the treatment of liver cancer, and the most important limitation is the heat sink effect, in which the lower temperature is not sufficient to inactivate tumor cells and may cause incomplete ablation. [ 50 ] Lehmann et al [ 51 ] used in vitro experiments to confirm that a minimum vascular flow of 1 mL/min could cause an obvious heat sink effect during the RFA of isolated liver. A single-center retrospective study by Lin et al [ 52 ] found that the heat sink effect caused by blood vessels was an important factor of the recurrence of liver malignant tumors after RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, RFA still exhibits some limitations in the treatment of liver cancer, and the most important limitation is the heat sink effect, in which the lower temperature is not sufficient to inactivate tumor cells and may cause incomplete ablation. [ 50 ] Lehmann et al [ 51 ] used in vitro experiments to confirm that a minimum vascular flow of 1 mL/min could cause an obvious heat sink effect during the RFA of isolated liver. A single-center retrospective study by Lin et al [ 52 ] found that the heat sink effect caused by blood vessels was an important factor of the recurrence of liver malignant tumors after RFA.…”
Section: Discussionmentioning
confidence: 99%
“…The ablation effect of the metastasis near great vessels is not satisfactory. This may be due to the heat sink effect; that is, the blood vessels in the liver take away some of the heat from the thermal ablation zone, which will cause local cooling and prevent complete ablation[ 38 , 39 ]. Existing studies have suggested that ablation treatment can effectively treat CLM, especially when the metastasis is ≤ 3 cm; however, when the lesion is larger than 5 cm, it is difficult to achieve complete necrosis using ablation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study was performed with a glass tube that simulated a liver vessel to achieve a standardized setup. The isolating properties of the glass tube can be neglected, as it was situated outside of the electrical field of the applicators [9], [11], [12], [26]. Energy transmission took place at the position of the glass tube by direct temperature transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Stopping the peristaltic pump simulated a Pringle maneuver. The test settings, which are specified above, corresponded to parameters that were established within our research group [9], [11], [12].…”
Section: Methodsmentioning
confidence: 99%